A new clinical tool for assessing numerical abilities in neurological diseases: numerical activities of daily living - Semenza, Carlo; Meneghello, Francesca; Arcara, Giorgio; Burgio, Francesca; Gnoato, Francesca; Facchini, Silvia; Benavides-Varela, Silvia; Clementi, Maurizio; Butterworth, Brian (Frontiers in Aging Neuroscience, 2014)
The aim of this study was to build an instrument, the Numerical Activities of Daily Living (NADL), designed to identify the specific impairments in numerical functions that may cause problems in everyday life. These impairments go beyond what can be inferred from the available scales evaluating activities of daily living in general, and are not adequately captured by measures of the general deterioration of cognitive functions as assessed by standard clinical instruments like the MMSE and MoCA. We assessed a control group (n = 148) and a patient group affected by a wide variety of neurological conditions (n = 175,) with NADL along with IADL, MMSE, and MoCA. The NADL battery was found to have satisfactory construct validity and reliability, across a wide age range. This enabled us to calculate appropriate criteria for impairment that took into account age and education. It was found that neurological patients tended to overestimate their abilities as compared to the judgment made by their caregivers, assessed with objective tests of numerical abilities.